Tubular collagen scaffolds with radial elasticity for hollow organ regeneration. (1st April 2017) - Versteegden, Luuk R.; van Kampen, Kenny A.; Janke, Heinz P.; Tiemessen, Dorien M.; Hoogenkamp, Henk R.; Hafmans, Theo G.; Roozen, Edwin A.; Lomme, Roger M.; van Goor, Harry; Oosterwijk, Egbert; Feitz, Wout F.; van Kuppevelt, Toin H.; et al.
Graphical abstract: Abstract: Tubular collagen scaffolds have been used for the repair of damaged hollow organs in regenerative medicine, but they generally lack the ability to reversibly expand in radial direction, a physiological characteristic seen in many native tubular organs. In this study, tubular collagen scaffolds were prepared that display a shape recovery effect and therefore exhibit radial elasticity. Scaffolds were constructed by compression of fibrillar collagen around a star-shaped mandrel, mimicking folds in a lumen, a typical characteristic of empty tubular hollow organs, such as ureter or urethra. Shape recovery effect was introduced by in situ fixation using a star-shaped mandrel, 3D-printed clamps and cytocompatible carbodiimide crosslinking. Prepared scaffolds expanded upon increase of luminal pressure and closed to the star-shaped conformation after removal of pressure. In this study, we applied this method to construct a scaffold mimicking the dynamics of human urethra. Radial expansion and closure of the scaffold could be iteratively performed for at least 1000 cycles, burst pressure being 132 ± 22 mmHg. Scaffolds were seeded with human epithelial cells and cultured in a bioreactor under dynamic conditions mimicking urination (pulse flow of 21 s every 2 h). Cells adhered and formed a closed luminal layer that resisted flow conditions. In conclusion, a new type of a tubular collagen scaffold has been constructed with radial elastic-like characteristics based on the shape of the scaffold, and enabling the scaffold to reversibly expand upon increase in luminal pressure. These scaffolds may be useful for regenerative medicine of tubular organs. Statement of Significance: In this paper, a new type I collagen-based tubular scaffold is presented that possesses intrinsic radial elasticity. This characteristic is key to the functioning of a number of tubular organs including blood vessels and organs of the gastrointestinal and urogenital tract. The scaffold was given a star-shaped lumen by physical compression and chemical crosslinking, mimicking the folding pattern observed in many tubular organs. In rest, the lumen is closed but it opens upon increase of luminal pressure, e.g. when fluids pass. Human epithelial cells seeded on the luminal side adhered well and were compatible with voiding dynamics in a bioreactor. Collagen scaffolds with radial elasticity may be useful in the regeneration of dynamic tubular organs.